HUBUNGAN PENGETAHUAN ORANG TUA DENGAN TINGKAT KEMANDIRIAN ACTIVITY OF DAILY LIVING ANAK RETARDASI MENTAL: THE RELATIONSHIP BETWEEN THE KNOWLEDGE OF PARENTS AND THE LEVELS OF INDEPENDENCE ACTIVITY OF DAILY LIVING CHILDREN WITH MENTAL RETARDATION - Martariani, Ita; Anom, Dewa Gede; Dewi, Ni Luh Putu Thrisna (Stikes Wira Medika Bali, 2020)
Mental retardation is a state of mental development that is stalled or incomplete which is mainly marked by the occurrence of skill constraints during the development period, so that it affects the overall level of intelligence, for example cognitive, language, motoric, and social abilities. Skills constraints during the development period cause parents to be confused, sad, frustrated and even refuse the presence of children who are mentally retarded. The purpose of this study was to determine the correlation of parental knowledge with the level of independence of Activity of Daily Living mentally retarded children in the Mental Clinic of UPTD Bali Provincial Mental Hospital. The sampling method is Non-Probability sampling type Consecutive sampling. The number of samples are 83 respondent parents who have mentally retarded children. Data analysis using spearman rank test. Statistical test results found that r count = 0.789 and p-value = 0.000. Its means that there is correlated between parents knowledge and the level of independence of the mental retardation Activity of Daily Living children with the strength of strong correlation and the direction of positive correlation, hence it is suggested to parents in order to increase knowledge for increase the independence of the ADL mental retardation